Korelasi Inovasi dan Kinerja pada Industri Kecil dan Menengah: Kajian Meta-Analisis - Trifandi Lasalewo; Avin Fadilla Helmi (Faculty of Psychology Universitas Gadjah Mada, 2014)
The effect of innovation on performance of Small and Medium Industries (SMIs) draws a great ofattention from researchers and practitioners to study further. Based on empirical findings, it is foundout that the correlation between innovation and performance is dependent on context, that is theinnovation does not affect the performance of a company or indicated negative implication betweeninnovation and performance. Meanwhile, other researches reported positive effects of innovation andperformance. The review of researches on the correlation between innovation and SMIs performanceshows contradictory results.The meta-analytical study is aimed at investigating further thecorrelation between innovation and performance on SMI based on researches published between 2004and 2013 in 5 continents (Australia, Asia, Europe, Africa and America). The independent variablewas innovation and the dependent variable was performance, while the moderators variable consistedof the year of the research and the location of survei. The result of the meta-analytical study on thecorrelation between innovation and performance indicated a positive correlation with mean 0.459and the standard deviation 0.168 on 95% confidence interval.